The Role of Entrepreneurs' Self-Efficacy and Alertness in Green Logistics Management for Sustainability in SMEs - Boonnual, Chutimant; Buasarabun, Chaninat; Lalaeng, Chanyaphak (Journal of Ecohumanism, 2025)
This research aims to check the consistency and develop a model. It also explores the role of mediating variables and moderating variables that affects Sustainability Performance. The population used in this study was a group of small and medium-sized enterprises (SMEs), a sample of 250 (Wiratchai, 1999). Using the Smart PLS model, a two-stage approach was used for direct path, mediation and mediation effect analysis with high-dimensional latent variables. The results of the study found that GLM, EA, and ESE has a direct positive effect on SP. EA and ESE has a direct positive effect on GLM. The results of the mediation influence test found that, EA impact GLM through the mediation of ESE, EA impact SP through the mediation of ESE. But, no mediating role was discovered between GLM impact SP through the mediation of ESE. The results of mediation influence test found that, EA impact SP through the moderator of ESE, EA impact GLM through the moderator of ESE.